Synthesis, physical-chemical and biological properties of 1,8-disubstituted of theobromine. ІV. 8-R-thioderivatives of 1-p-methylbenzyltheobronine - D. G. Ivanchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The problem of biologically active compounds searching amidst xanthine derivatives is a crucial one and is an issue for long-term investigation.